Bidding with Securities: Auctions and Security Design - DeMarzo, Peter M; Kremer, Ilan; Skrzypacz, Andrzej (American Economic Review, 2005)
We study security-bid auctions in which bidders compete for an asset by bidding with securities whose payments are contingent on the asset's realized value. In formal security-bid auctions, the seller restricts the security design to an ordered set and uses a standard auction format (e.g., first- or second-price). In informal settings, bidders offer arbitrary securities and the seller chooses the most attractive bid, based on his beliefs, ex post. We characterize equilibrium and show that steeper securities yield higher revenues, that auction formats can be ranked based on the security design, and that informal auctions lead to the lowest possible revenues.